OPTOELECTRONIC SYSTEMS IN DIAGNOSTIC AND MEASUREMENT APPLICATIONS - Kotyra, Andrzej (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The article presents brief survey of optical diagnostic methods used especially in the case of pulverized coal combustion process as well as coal – biomass blends, that was developed in Institute of Electronic and Information Technology. Lublin University of Technology. Special attention was paid to the methods that can be applied in harsh conditions.